2015
DOI: 10.5539/gjhs.v8n7p240
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Pre- and Post-Stenting Fractional Flow Reserve for Predicting Mid-Term Stent Restenosis Following Percutaneous Coronary Intervention (PCI)

Abstract: Measuring fractional flow reserve (FFR) in percutaneous coronary intervention (PCI) has predictive value for PCI outcome. We decided to examine the utility of pre- and post-stenting FFR as a predictor of 6-month stent restenosis as well as MACE (major adverse cardiac events). Pre- and post-stenting FFR values were measured for 60 PCI patients. Within 6 months after stenting, all patients were followed for assessment of cardiac MACE including myocardial infarction, unstable angina, or positive exercise test. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The tendency for the incidence of MI was more in patients with insulin. From another point of view that has similarities to DM as an independent factor for restenosis, observations were made (Rai et al, 2015). Regarding the FFR, it was suggested that the post-stent FFR could be used to predict restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for the incidence of MI was more in patients with insulin. From another point of view that has similarities to DM as an independent factor for restenosis, observations were made (Rai et al, 2015). Regarding the FFR, it was suggested that the post-stent FFR could be used to predict restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Published values for overall mean or median final post‐PCI FFR results range from 0.84 to 0.95 . The proportion of patients actually achieving a final FFR ≥0.90 varies widely between studies and ranges from 37% to 93% .…”
Section: Introductionmentioning
confidence: 99%